3D Whole-Brain Perfusion Quantification using Pseudo-Continuous Arterial Spin Labeling MRI at Multiple Post-Labeling Delays: Accounting for Both Arterial Transit Time and Impulse Response Function - Qin, Qin (2013)
Measurement of cerebral blood flow (CBF) with whole-brain coverage is challenging in terms of both acquisition and quantitative analysis. In order to fit the ASL-based perfusion kinetic curves, an empirical 3-parameter model that characterizes the effective impulse response function (IRF) is introduced, which allows determination of CBF, arterial transit time (ATT), and T(1,eff). The accuracy and precision of the proposed model is compared with more complicated models with 4 or 5 parameters through Monte Carlo simulations. Pseudo-continuous arterial spin labeling (PCASL) images were acquired on a clinical 3 Tesla scanner in 10 normal volunteers using a 3D multi-shot gradient- and spin-echo (GRASE) scheme at multiple post-labeling delays to sample the kinetic curves. Voxel-wise fitting was performed using the 3-parameter model and other models that contain 2, 4 or 5 unknown parameters. For the 2-parameter model, T(1,eff) values close to tissue and blood were assumed separately. Standard statistical analysis was conducted to compare these fitting models in various brain regions. The fitted results indicate that: 1) the estimated CBF values using the 2-parameter model show appreciable dependence on the assumed T(1,eff) values; 2) the proposed 3-parameter model achieves the optimal balance between the goodness of fit and the model complexity when compared among the models with explicit IRF fitting; 3) both the 2-parameter model using fixed blood T(1) values for T(1,eff) and the 3-parameter model provide reasonable fitting results. Using the proposed 3-parameter model, the estimated CBF values (46±14 mL/100g/min) and ATT values (ATT = 1.4±0.3 s) averaged from different brain regions are close to the literature reports; the estimated T(1,eff) values (T(1,eff) = 1.9±0.4 s) are higher than the tissue T(1) values, possibly reflecting a contribution from the microvascular arterial blood compartment.